1996
DOI: 10.1210/endo.137.7.8770927
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that type III iodothyronine deiodinase in rat astrocyte is a selenoprotein.

Abstract: A type III iodothyronine deiodinase (D-III) that inactivates thyroid hormones has been recently cloned and identified as a selenoprotein in neonatal rat skin. However, selenium (Se) deficiency does not affect the D-III activity in the rat placenta and decreases the D-III in the rat brain only slightly. This study examines the effect of Se on the D-III activity in cultures of rat brain astrocytes. Astrocytes were depleted in Se by maintaining them in Se-free chemically defined medium for 7 days. These condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 26 publications
3
19
0
Order By: Relevance
“…Although differences in the rates of turnover of these proteins may be responsible in part for these observations, the results support the emerging concept that there is a hierarchy of expression of selenoproteins within a given cell or tissue (49,50). We have previously reported similar preferential expression of DIII after selenium repletion of glial cells (51). The mechanisms responsible for this differential utilization of selenium within the cell remain poorly defined, but could be secondary to selective alterations in selenoprotein mRNA levels induced by selenium deficiency (52)(53)(54) or differences in the translational efficiency of deiodinase versus GPx mRNAs.…”
Section: Discussionsupporting
confidence: 77%
“…Although differences in the rates of turnover of these proteins may be responsible in part for these observations, the results support the emerging concept that there is a hierarchy of expression of selenoproteins within a given cell or tissue (49,50). We have previously reported similar preferential expression of DIII after selenium repletion of glial cells (51). The mechanisms responsible for this differential utilization of selenium within the cell remain poorly defined, but could be secondary to selective alterations in selenoprotein mRNA levels induced by selenium deficiency (52)(53)(54) or differences in the translational efficiency of deiodinase versus GPx mRNAs.…”
Section: Discussionsupporting
confidence: 77%
“…Even though there is an increased requirement for selenium during pregnancy, decreased selenium levels during this physiological stage have previously been reported [37]. Similar to previous animal studies, our study also showed that the placental D3 expression level was not affected by the maternal serum selenium level [16,17,38].…”
Section: Discussionsupporting
confidence: 90%
“…Chu et al (1999) found that the addition of RA increased the expression of GPX2 mRNA in a human mammary cell line, and other in vitro studies have shown that RA increased the activity of iodothyronine deiodinases (ID1 and ID3) in cell systems (Ramauge et al 1996;Menth et al 2005). However, very little data is available to explore the effects of RA on the bovine mammary epithelial cells (BMEC).…”
Section: Introductionmentioning
confidence: 99%